Devenir époux/épouse. Les premiers amours comme socialisation à une conjugalité violente (Lifou, Kanaky-Nouvelle-Calédonie) - Hélène Nicolas (Genre, Sexualité et Société)
Among the Kanak women of Lifu, one third declared that they have been harassed physically or sexually in the previous year (ENVEFF, 2004). This article shows that romantic and sexual experiences during “youth” are a socialization to this violent conjugality. During this period, acts of physical and sexual violence are facilitated by the representation of pre-marital sexuality as asocial and violent, the taboo that situates sexual encounters in the margin of public spaces as well as an ambivalent norm of virginity and fertility for young women. Despite the spread of self-defense strategies among young women, the Lifu people also learn that love, sexuality and violence are usually closely related.